Was the God of Israel Worshipped on the Sinai Peninsula? In the Footsteps of the Israelites and Related Peoples at the time of the Exodus from Egypt - Gert van der Veen, Pieter (2024)
Fil: Gert van der Veen, Pieter. Universität Mainz; Alemania